Phenylboronic acid conjugated mPEG-b-PCL micelles as DOX carriers for enhanced drug encapsulation and controlled drug release - Yin, Wang; Wang, Yixiu; Xiao, Yan; Mao, Anrong; Lang, Meidong (European polymer journal, 2022)
[Display omitted] •Block polymers with three pendant groups were prepared by ROP and post-modification.•PBA-modified DOX-loaded micelles have the highest drug loading efficiency.•PBA-modified DOX-loaded micelles can be selectively release DOX by triggering with H2O2.•PBA-modified DOX-loaded micelles have the highest anti-cancer efficacy in vitro. Polymeric micelles represent an important delivery platform for hydrophobic drugs, but limited by unsatisfactory drug loading, micellar stability and controlled release. Herein, poly(ɛ-caprolactone) block copolymers with three different pendant groups (tert-butyl formate, carboxylate, and phenylboronic acid formate) were prepared by organocatalytic ring-opening polymerization and post modification. All three block polymers with different pendant groups can form micelles by self-assembly with uniform size of approximately 100 nm and narrow distribution. In particular, the DOX-loaded micelles with phenylboronic acid (PBA) conjugation exhibit high encapsulation efficiency (greater than95 %) and colloidal stability of constant basic particle size over a week. Besides, compared to the other two groups of drug-loaded micelles, the PBA-modified drug-loaded micelles can selectively release drugs by triggering with H2O2. After treatment with 100 μM H2O2, the cumulative drug release from micelles increased by 2.5 times in PBS solution at pH 7.4. More importantly, drug-loaded micelles of PBA modifying can be selectively released according to the high level of reactive oxygen species in cancer cells, which could improve anti-cancer efficacy and reduce toxic side effects. The micelle covalently modified by PBA was demonstrated as a promising drug carrier for DOX delivery.